Evolution of dental implants through the work of per-ingvar branemark: A systematic review - Sunil Kumar Mishra; Ramesh Chowdhary (Wolters Kluwer Medknow Publications, 2020)
Purpose: This systematic review has been undertaken to highlight the unforgettable contributions of Prof. Brånemark Per-Ingvar (PI). It could be understood that reviewing his work would give an idea of growth of this treatment modality. Materials and Methods: An electronic search on the PubMed/Medline, Ebscohost, and Cochrane database was done using search term "Brånemark PI" to identify his publications. Articles published in English and only related to implants and osseointegration were included. Screening of the titles and abstracts were done according to inclusion criteria and suitable studies were included in the review. Results: The initial literature search resulted in 187 articles, out of which 92 articles were excluded due to not meeting the inclusion criteria and 16 articles excluded due to non-availability of even abstract also. A total of 79 articles were finally included in this review. Conclusion: Brånemark PI had a great vision of future; who considered edentulism as equal to amputation and came up with the concept of osseointegrated implants to overcome them. The innovations of Brånemark had assured the world that it is very much possible to provide implant-supported prosthesis in any situations for the rehabilitation of the individuals.